THE EFFECT OF PROCESS ORIENTED GUIDED INQUIRY LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN CLASS XI MATERIALS - Elna Farlita Mendrofa; Marlinda Nilan Sari Rangkuti; Wasis Wuyung Wisnu Brata (Jurnal Pelita Pendidikan, 2022)
This research was motivated by the difficulties students face in understanding the material on cells. Specifically, 70% of the students' learning outcomes in cell material did not meet the Minimum Completeness Criteria, indicating a need for improvement in the learning process. To address this, innovative learning models were implemented. The study utilized a quasi-experimental design with a pretest and posttest control group design. The research sample was selected using purposive sampling techniques, resulting in two classes: Class XI MIPA 5 (Experimental Class) where the POGIL learning model was applied, and Class XI MIPA 6 (Control Class) where the conventional learning model was used. Data collection involved administering a test consisting of 20 multiple-choice questions. The mean scores for the control class were 37.91 and 67.63. Data analysis was conducted using the Paired Sample t-Test with SPSS Version 21 software. The results of the hypothesis testing revealed that the POGIL learning model had a significant effect on student learning outcomes in cell material for Class XI MIPA SMA N 12 Medan T.P. 2022/2023. The N-gain value for the experimental class was 0.71, falling within the high category, while the control class had an N-gain value of 0.46, categorizing it as medium. This indicates that the POGIL learning model had a greater impact on student learning outcomes in cell material for Class XI MIPA SMA N 12 Medan T.P. 2022/2023.